Malaysian consumers' awareness, perception, and attitude toward cosmetic products: Questionnaire development and pilot testing - Ayob, Ain; Awadh, Ammar Ihsan Jawad; Ab. Hadi, Hazrina; Md. Jaffri, Juliana; Jamshed, Shazia Qasim; Ahmad, Hawa Mas Azmar (Wolters Kluwer ‑ Medknow, 2016)
Background: Increased usage of cosmetic products has caused a growing concern about the safety of these products, and yet little is known about cosmetics from the consumers' perspective. Hence, this study's aim is to develop a valid and reliable tool for assessing consumers' awareness, perceptions, and attitudes toward cosmetic products. Materials and Methods: A questionnaire was developed in the English language based on information collected from a literature search, in-depth interviews conducted with consumers prior to this study and consultations with experts. Subsequently, the questionnaire was subjected to translation, validation, and test-retest reliability. A final version of the questionnaire was piloted among 66 consumers via convenient sampling. A descriptive analysis was performed, and the internal consistency and the differences between variables in the questionnaire were analyzed. Results: The developed and translated questionnaire produced repeatable data for each of the domains (Spearman's correlation ≥ 0.7, P < 0.001). The internal consistency for awareness, perceptions and attitudes indicates good internal consistency (Cronbach's alpha value of more than 0.7 for each domain). Significant differences were found between the perception scores for the race, religion, and monthly expenses for cosmetic products, respectively, and the same pattern was found for the attitude scores, but monthly expenses for cosmetic products was replaced by monthly income. Conclusion: The results achieved via the Bahasa Malaysia questionnaire indicated that the developed and translated questionnaire can be used as a valid and reliable tool for assessing consumers' awareness, perceptions, and attitudes toward cosmetic products in Malaysia in future studies.